2017
DOI: 10.4236/ojd.2017.61001
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Depressive Disorder or Dysthymia: An Overview of Assessment and Treatment Approaches

Abstract: Persistent depressive disorder or dysthymia is a recurrent depressive disorder with no clearly demarcated episodes. Onset is insidious and can occur in adolescence or adulthood. Dysthymia frequently remains unrecognized and undiagnosed for years. Co-morbid major depression, anxiety, personality, somatoform and substance abuse disorders are common. Symptoms center on sad mood, pessimism and hopelessness. Sufferers experience significant functional impairment and are at risk of death by suicide. Those most at ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…People who adopt better habits of nutrition, physical exercise, relaxation/sleep, drug use, and social contact are considered to experience an improvement in their depression. This practice, known as lifestyle medicine, may be a kind of treatment for depression [1], health Professionals can let clients to consider make some changes in their practices in these areas. There is a considerable link between quality of life and suicide rates, with those who have a worse quality of life having greater rates of suicidal thoughts.…”
Section: Cognitive Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…People who adopt better habits of nutrition, physical exercise, relaxation/sleep, drug use, and social contact are considered to experience an improvement in their depression. This practice, known as lifestyle medicine, may be a kind of treatment for depression [1], health Professionals can let clients to consider make some changes in their practices in these areas. There is a considerable link between quality of life and suicide rates, with those who have a worse quality of life having greater rates of suicidal thoughts.…”
Section: Cognitive Therapymentioning
confidence: 99%
“…According to DSM 5, dysthymia is another name for persistent depressive illness, generally known as PDD, present for most days of the two years. Many patients who suffer from persistent depressive disorder also suffer from major depressive disorder (MDD); the combination of these two conditions is referred to as double depression [1]. Major depressive disorder and persistent depressive disorder share so many similarities in terms of symptoms, causes, and treatments that the two depressive disorders are often discussed together.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Iranian population, the alpha coefficient was reported at 92% for outpatients, and its validity has been reported between 70%-90% [28]. The Cornell Dysthymia Rating Scale (CDRS) [29] is used to assess the frequency and severity of depression symptoms [14]. Internal stability in foreign studies has been between 64% and 83%, and concurrent and content validity indicated that it is a valuable tool [30].…”
Section: Quantitative Toolsmentioning
confidence: 99%
“…The patient had very low self-esteem and experienced painful events such as physical abuse and repeated humiliation by the father, being detained in prison, parental divorce, and a 10-year history of substance abuse. According to literature, the early onset of this disorder [13] is frequently associated with anxiety disorders, substance abuse, somatoform disorders, chronic illnesses [14], personality disorders, and parental abusive behaviors, particularly during childhood [15]. Disturbing and inconvenient memories are present in 76%-90% of adults suffering from depression [16] and are alive and emotional [17] accompanied by anxiety and negative affections [18].…”
Section: Introductionmentioning
confidence: 99%